In Situ Stress Distribution in Cretaceous Ultra-Deep Gas Field From 1D Mechanical Earth Model and 3D Heterogeneous Geomechanical Model, Kuqa Depression, Tarim Basin, NW China - Xu, Ke; Zhang, Hui; Dong, Ruixia; Ju, Wei; Xie, Yani; Cui, Deyu; Fang, Lu; Yuan, Fang; Lai, Shujun; Liang, Jingrui; Zhang, Wei; Zhao, Bin (Frontiers in Earth Science, 2022)
The Kuqa Depression boasts rich Cretaceous ultra-deep hydrocarbon resources; however, it is in complex geological conditions. At present, sufficient understandings on the in situ stress distribution and influencing factors are lacked, which restricts the process of hydrocarbon exploitation. Therefore, in this study, the Bozi gas field is selected as an example, a 1D Mechanical Earth Model (1D HEM) is established with drilling data and logging data through geomechanical method to clarify the in situ stress distribution of the wellbore. A 3D Heterogeneous Geomechanical Model (3D HGM) is established with the constraint of 1D HEM to clarify the distribution characteristics of 3D in situ stress field in the Bozi gas field and discuss its influencing factors. The results show that: (1) The Bozi gas field is in an extremely strong in situ stress condition with high stress values. The minimum horizontal principal stress (Sh) of the Cretaceous system is 153~180MPa, and the maximum horizontal principal stress (SH) is nearly 200MPa; (2) The in situ stress in the Bozi gas field has obvious vertical stratification characteristics, which can be divided into three stress sequences of “low-high-low”, with great differences in interlayer stress; (3) The in situ stress distribution of Bozi gas field is greatly affected by the types of faulted anticline. Different types indicate different stress distribution; (4) Within the influence range of overthrusts, the in situ stress in footwall is lower than that of hanging wall. The greater the fault offset, the greater the in situ stress difference between hanging wall and footwall. Moreover, the lower of stress in footwall, the higher degree of overthrust, the larger the range of footwall stress area; (5) The means of highly deviated wells is more helpful to Bozi gas field for hydrocarbon exploitation.